2022
DOI: 10.1021/jacs.2c05601
|View full text |Cite
|
Sign up to set email alerts
|

Template-Free Assembly of Functional RNAs by Loop-Closing Ligation

Abstract: The first ribozymes are thought to have emerged at a time when RNA replication proceeded via nonenzymatic template copying processes. However, functional RNAs have stable folded structures, and such structures are much more difficult to copy than short unstructured RNAs. How can these conflicting requirements be reconciled? Also, how can the inhibition of ribozyme function by complementary template strands be avoided or minimized? Here, we show that short RNA duplexes with single-stranded overhangs can be conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…Following this observation, we predict that a system composed by a large collection of duplexes exposing only short toeholds will undergo an exceptionally long equilibration process. This finding is particularly relevant in the context of models for the nonenzymatic replication of genetic information, which is believed to be driven by chemical reactions occurring in highly heterogeneous and complex mixtures of oligoribonucleotides ( 12 , 69 ).…”
Section: Discussionmentioning
confidence: 97%
“…Following this observation, we predict that a system composed by a large collection of duplexes exposing only short toeholds will undergo an exceptionally long equilibration process. This finding is particularly relevant in the context of models for the nonenzymatic replication of genetic information, which is believed to be driven by chemical reactions occurring in highly heterogeneous and complex mixtures of oligoribonucleotides ( 12 , 69 ).…”
Section: Discussionmentioning
confidence: 97%
“…Oligonucleotides of this length can then be assembled into functional ribozymes, either by splinted ligation 15 or by iterated loop-closing ligation. 16 These ribozyme building blocks could be the end products of one or potentially multiple virtual circular genomes replicating together in a protocell in a prebiotically plausible environment. Here, we explore a model VCG system with a 12-nt long virtual genome represented by 247 different oligonucleotides, which range from 2 to 12 nucleotides in length.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Partially overlapping pairs of such oligonucleotides can anneal with each other, after which loop-closing ligation can lead to the formation of stem-loop structures. 12 The iteration of such processes could then lead to the assembly of complex structured RNAs, including ribozymes.…”
Section: Discussionmentioning
confidence: 99%
“…Our lab has recently demonstrated that splinted ligation and loop-closing ligation can form functional ribozymes from short oligonucleotides. 11,12 However, even the replication of shorter oligonucleotides faces problems that can lead to information loss at both ends of the sequence. First, the nonenzymatic copying of the last base of a sequence by primer extension is known to be very slow relative to the copying of internal nucleotides, 13 which could lead to progressive loss of 3ʹ-sequences over cycles of replication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation